Spontaneous Primary Squamous Cell Carcinoma of the Lung in a Rhesus Macaque (Macaca mulatta) - Jean, Sherrie M (American Association for Laboratory Animal Science, 2011)
A 3-y-old male rhesus macaque (Macaca mulatta) was noticed to be lethargic in the compound. Physical exam revealed cyanotic mucous membranes, dyspnea, bilateral harsh lung sounds, wheezing on expiration, and a firm mass possibly associated with the liver. Radiographs revealed bilateral soft tissue opacities in the thorax. Due to poor prognosis, the rhesus was euthanized, and a necropsy was performed. Both right and left lung lobes were consolidated and had multifocal white–tan masses. On cut section, the masses were firm, had areas of necrosis, hemorrhage, and often contained a tenacious exudate. Masses were identified in the liver and both kidneys. Given the morphologic features of the neoplasm, a diagnosis of squamous cell carcinoma was made. Immunohistochemistry staining for thyroid transcription factor, a nuclear transcription factor normally found in lung, thyroid, and tumors arising from either of those tissues, confirmed that the masses originated from the lung. Malignant primary lung tumors are divided into 8 main histologic subtypes: squamous cell carcinoma, small-cell carcinoma, large-cell carcinoma, adenocarcinoma, adenosquamous carcinoma, sarcomatoid carcinoma, carcinoid tumor, and salivary gland tumors. Clinical signs associated with lung tumors include, but are not limited to, dyspnea, coughing, hemoptysis, lethargy, anorexia, and weight loss. Although squamous cell carcinoma will be low on the differential list for these clinical signs, we encourage clinicians and researchers to not rule it out solely based on incidence and age of the animal.